Acute Kidney Injury after ingestion of Star fruit juice in patients with previous history of acute kidney injury: Two case reports (Journal of Shaheed Suhrawardy Medical College, 2017)
Acute kidney injury can occur due to various reasons. In this case report two cases of acute kidney injury (AKI) were reported after ingestion of 250 ml of starfruit juice presented. In both cases features of nephrotoxicity and neurotoxicity were found and there was mild to moderate rise in serum creatinine. Routine and microscopic examination of urine showed mild degree of proteinuria, no other active urinary sediment was found except calcium oxalate crystals. Renal biopsy was done in both cases which showed features of acute tubular necrosis. These two patients were treated symptomatically and discharged with normal serum creatinine. There is no case report of acute kidney injury due to star fruit ingestion in Bangladesh. Star fruit is very popular, cheap and easily available. But its nephrotoxic effect is not known to general population. These two case reports might be a first time message to the nation.J Shaheed Suhrawardy Med Coll, 2015; 7(1):33-35